2011
DOI: 10.1021/ja210029w
|View full text |Cite
|
Sign up to set email alerts
|

Competition between the Charge Transfer State and the Singlet States of Donor or Acceptor Limiting the Efficiency in Polymer:Fullerene Solar Cells

Abstract: We study the appearance and energy of the charge transfer (CT) state using measurements of Electroluminescence (EL) and Photoluminescence (PL) in blend films of high-performance polymers with fullerene acceptors. EL spectroscopy provides a direct probe of the energy of the interfacial states without the need to rely on the LUMO and HOMO energies as estimated in pristine materials. For each polymer, we use different fullerenes with varying LUMO levels as electron acceptors, in order to vary the energy of the CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
298
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(320 citation statements)
references
References 77 publications
17
298
0
Order By: Relevance
“…This observation suggests that the small LUMO energy offset may not be the limiting factor, but instead a small HOMO offset limits the performance, possibly by enabling a recombination channel through the fullerene exciton, as others have proposed. 40 The problem is exacerbated in cells using ICBA since this material reduces the HOMO band offset, and the ICBA exciton is also at lower energy than the PC 60 BM exciton.…”
Section: Background and Measurement Methodologymentioning
confidence: 99%
“…This observation suggests that the small LUMO energy offset may not be the limiting factor, but instead a small HOMO offset limits the performance, possibly by enabling a recombination channel through the fullerene exciton, as others have proposed. 40 The problem is exacerbated in cells using ICBA since this material reduces the HOMO band offset, and the ICBA exciton is also at lower energy than the PC 60 BM exciton.…”
Section: Background and Measurement Methodologymentioning
confidence: 99%
“…CT state EL was first reported by Kim et al, 48 and then also observed by other groups (Figure 2c). 46,47,49 Although the EL of the CT state is in the same spectral range as the PL, the EL peak usually shows slight redshift compared with the PL peak. 50 In addition, the EL peak could also show slight blueshift with increasing injection current or applied voltage.…”
Section: Electroluminescencementioning
confidence: 99%
“…The driving force for charge separation for these excitons on the fullerene, Δ E HOMO , is smaller than Δ E LUMO in this case and could be insuffi cient for charge generation. [ 36 ] In blends with high-bandgap polymers, the fullerene singlet can also act as an additional recombination channel through activation of the fullerene singlet that appears at Δ E HOMO < 0.35 eV and can reduce fi ll factor as well as open-circuit voltage. [ 36 ] …”
Section: Full Papermentioning
confidence: 99%
“…[ 36 ] In blends with high-bandgap polymers, the fullerene singlet can also act as an additional recombination channel through activation of the fullerene singlet that appears at Δ E HOMO < 0.35 eV and can reduce fi ll factor as well as open-circuit voltage. [ 36 ] …”
Section: Full Papermentioning
confidence: 99%